Complex Regional Pain Syndrome Type 1 in Both Lower Extremities, Resistant to Treatment: A Case Report - Özlem Altındağ; Ali Aydeniz; Savaş Gürsoy; Türkan Harunlar Bukan (Archives of Rheumatology, 2009)
Complex regional pain syndrome type 1 (CRPS-1) is characterized by pain, vasomotor and sudomotor changes and trophic disturbances. It may develop as a result of trauma, especially extremity fractures and surgery. Although the pathogenesis of CRPS-1 is not exactly clear, abnormal sympathetic nerve activity may be a potential etiological factor. Occurrence of CRPS-1 in the lower extremity with bilateral involvement is a very rare condition. Calcitonin, bisphosphonates and analgesics can be used in the management of these cases. A case of bilateral lower extremity CRPS-1 with rebellious pain is described and discussed in this paper. We suggest bilateral CRPS-1 may occur in the lower extremity and pregabalin may be an effective and alternative therapy in these patients. (Turk J Rheumatol 2009; 24: 103-5)